"Getting the Point" of Literature: Relations Between Processing and Interpretation. Issue 5 (3rd July 2016) - Burkett, Candice; Goldman, Susan R.
Abstract : Comparisons of literary experts and novices indicate that experts engage in interpretive processes to "get the point" during their reading of literary texts but novices do not. In two studies the reading and interpretive processes of literary novices (undergraduates with no formal training in literature study) were elicited through think-alouds during reading and a post-reading interview task. Twenty undergraduates read one of two short stories in each of two studies ( n  = 80). Both studies used the same methodology, except that the instructions for Study 2 emphasized the importance of interpretation when reading literary short stories. Results indicate that literary novices noticed cues to interpretive meaning during reading but were more likely to provide literary interpretations (symbolic and thematic) during the interview task as compared with when reading (Study 1 and 2) and when the instructions emphasized interpretation (Study 2 as compared with Study 1). In both studies there were positive relationships between elaborative processing during reading and (1) providing interpretations during reading and thinking aloud and (2) producing prompted interpretations during the post-reading interview task. The present studies provide evidence that literary novices can and do generate literary interpretations, albeit less sophisticated than those experts would likely generate. Further, elaborative processing during reading was positively related to interpretations. Implications for instruction to enhance literary interpretations are discussed.